Reproductive outcomes following robotic myomectomy - Shaia, Kathryn L.; Sekhon, Lucky H.; Rosen, Leigh; Robbins, Alicia; Astill, Nicole; Ascher-Walsh, Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To assess pregnancy outcomes of patients following robotic myomectomy. Methods: Retrospective chart review was performed of 336 patients following robotic myomectomy at a university hospital from June 2006 to May 2013. Patients were called to obtain delivery outcomes. Results: Three hundred and thirty-six women had the following: mean age of 41.97 +/- 12.3 years (range 24-55), mean BMI of 24.6 +/- 4.96, mean of 3.37 +/- 3.1 fibroids removed (range 1-21), and mean weight of 352.28 +/- 339.56 grams of fibroids removed. Approximately 66.9% (N=250) provided pregnancy outcome data with 119 (47.6%) attempting pregnancy after surgery. Eighty-three (69.7%) achieved a total of 91 pregnancies. Less than half of these patients underwent cesarean section, and no cases of uterine rupture. Eighty-seven patients had known infertility pre-surgery; 22 underwent intrauterine insemination resulting in 12 pregnancies, and 34 underwent in vitro fertilization resulting in 25 pregnancies. A total of 53 (60.9%) of patients with infertility achieved 60 total pregnancies. Conclusions: The fertility rate after robotic myomectomy for patients attempting to conceive (69.7%) and for those with known infertility who continued to attempt pregnancy postoperatively (60.9%) were similar. There was a low incidence of complications associated with pregnancies conceived after robotic myomectomy.